(untitled) (Journal of Nepal Geological Society, 2018)
The Gorkha earthquake of April 25, 2015 has caused many landslides along the Trishuli River in the Rasuwa District. A numerical approach has been taken to assess the remaining risk of landslides. The debris mass movements are described in simulations with only three parameters, namely, the critical angle if, Gauckler–Manning roughness coefficient n, and angle of repose id. The optimum set of these three parameters, obtained through a batch of numerical simulations to minimize the prediction error, was then used to identify locations of unstable colluvium deposits remaining along gullies on steep valley walls of the Trishuli River.